Pancreatic neuroendocrine neoplasms: survival trend analysis of a comprehensive center - Sara Coelho; Cláudia Costa; Ana Paula Santos; Pedro Souteiro; Joana Oliveira; Isabel Azevedo; Isabel Torres; Maria José Bento (Endocrine Oncology, 2023)
Objectives: Therapeutic options for pancreatic neuroendocrine neoplasia (Pan-NEN) have increased over the last decade. We aim to understand the evolution of the prognosis of patients with diagnosis of Pan-NEN within a 12-year period, considering the implementation of new treatments. Methods: This study is a retrospective cohort study of patients diagnosed with Pan-NENs between 2006 and 2017. Survival outcome estimates were calculated by Kaplan–Meier method. The impact of baseline clinicopathological characteristics on survival was explored with the use of Cox proportional hazard model. Results: Of the 97 patients, 77 (79.9%) had well-differentiated neuroendocrine tumor (NET) according to WHO 2010 classification, and 52 (53.6%) had l ocalized or locoregional disease. There were no differences between clinicopathological characteristics and survival outcomes when comparing patients diagnosed between 2006–2011 and 2012–2017. Neuroendocrine carcinoma – HR 2.76, 95% CI 1.17–6.55 – and stages III and IV at diagnosis were independent poor prognostic factors – HR 6.02, 95% CI 2.22–16.33 and HR 6.93, 95% CI 2.94–16.32, respectively. Conclusions: The new therapeutic approaches did not induce better survival outcomes on Pan-NEN in recent years. This is possibly due to the indolent nature of NET grades 1 and 2, even metastatic, allowing patients to be submitted to new target therapies along their disease course.